Systemic inflammation and imbalance between endothelial injury and repair in patients with psoriasis are associated with preclinical atherosclerosis. (August 2015) - Pirro, Matteo; Stingeni, Luca; Vaudo, Gaetano; Mannarino, Massimo R; Ministrini, Stefano; Vonella, Marilisa; Hansel, Katharina; Bagaglia, Francesco; Alaeddin, Abdalkader; Lisi, Paolo; Mannarino, Elmo
Background: Systemic inflammation and imbalance between endothelial injury and repair, the latter referred to as vascular incompetence, are associated with atherosclerosis and cardiovascular risk. Psoriasis, an inflammatory disease of the skin, has been associated with atherosclerosis. We investigated whether, in psoriasis, inflammation and vascular incompetence are associated with carotid intima-media thickness (cIMT) irrespective of metabolic syndrome and other established cardiovascular risk factors. Methods: High sensitivity C-reactive protein (hsCRP), the ratio between endothelial microparticles (EMPs) and progenitors (EPCs), a marker of vascular incompetence, and cIMT were measured in 84 patients with psoriasis and 90 healthy controls, balanced for age, gender and the prevalence of metabolic syndrome. Results: Patients with psoriasis had higher hsCRP, EMP/EPC ratio and cIMT than controls. Patients with both psoriasis and metabolic syndrome had the highest hsCRP levels, psoriasis and metabolic syndrome being associated with a 3.1- and 2.6-fold increased risk of having high hsCRP levels, respectively. Logarithm transformed hsCRP and EMP/EPC ratio were predictors of high cIMT (odds ratio 3.8; 95% confidence interval 1.3–11.4; p  = 0.02 and odds ratio 8.7; 95% confidence interval 2.7–27.5; p  < 0.001, respectively) regardless of confounders. Patients with high hsCRP and EMP/EPC ratio had higher cIMT than those with none or at least one of risk variable. Conclusions: Patients with psoriasis have an increased burden of cardiovascular risk, including inflammation, vascular incompetence and early atherosclerosis. Increased hsCRP levels, possibly sustained by the inflammatory nature of psoriasis and metabolic syndrome, and vascular incompetence are associated with early carotid atherosclerosis, regardless of metabolic syndrome and other established cardiovascular risk factors.